Cycling Performance and Mechanistic Insights of Ferricyanide Electrolytes in Alkaline Redox Flow Batteries. Issue 15 (15th March 2023) - Hu, Maowei; Wang, Abigail P.; Luo, Jian; Wei, Qianhusn; Liu, T. Leo
Abstract: Ferrocyanide, such as K4 [Fe(CN)6 ], is one of the most popular cathode electrolyte (catholyte) materials in redox flow batteries. However, its chemical stability in alkaline redox flow batteries is debated. Mechanistic understandings at the molecular level are necessary to elucidate the cycling stability of K4 [Fe(CN)6 ] and its oxidized state (K3 [Fe(CN)6 ]) based electrolytes and guide their proper use in flow batteries for energy storage. Herein, a suite of battery tests and spectroscopic studies are presented to understand the chemical stability of K4 [Fe(CN)6 ] and its charged state, K3 [Fe(CN)6 ], at a variety of conditions. In a strong alkaline solution (pH 14), it is found that the balanced K4 [Fe(CN)6 ]/K3 [Fe(CN)6 ] half‐cell experiences a fast capacity decay under dark conditions. The studies reveal that the chemical reduction of K3 [Fe(CN)6 ] by a graphite electrode leads to the charge imbalance in the half‐cell cycling and is the major cause of the observed capacity decay. In addition, at pH 14, K3 [Fe(CN)6 ] undergoes a slow CN ‐ /OH ‐ exchange reaction. The dissociated CN ‐ ligand can chemically reduce K3 [Fe(CN)6 ] to K4 [Fe(CN)6 ] and it is converted to cyanate (OCN ‐ ) and further, decomposes into CO3 2‐ and NH3 . Ultimately, the irreversible chemical conversion of CN ‐ to OCN ‐ leads to the irreversible decomposition of K4 /K3 [Fe(CN)6 ] at pH 14. Abstract : Comprehensive electrochemical and spectroscopic studies are conducted to elucidate the degradation mechanism of ferricyanide at pH 14 and stress its proper use in aqueous redox flow batteries. The major degradation of ferricyanide is caused by a chemical redox reaction with a carbon electrode. The minor degradation pathway is attributed to the irreversible cyanide/hydroxide exchange and subsequent side reactions.